2018
DOI: 10.1176/appi.ajp.2018.17070792
|View full text |Cite|
|
Sign up to set email alerts
|

The Burden of Bereavement: Early-Onset Depression and Impairment in Youths Bereaved by Sudden Parental Death in a 7-Year Prospective Study

Abstract: Parental death increased the incidence of depression in offspring early in the course of bereavement. Early identification and treatment of depression in bereaved youths and augmentation of family resilience may protect against later sequelae of functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 40 publications
5
45
2
4
Order By: Relevance
“…Many studies have linked parental death with depression. 7,8 However, our data also confirm the negative effects on adult physical health. 6,[14][15][16][17][18] The study by Neeleman et al (2002) 15 analysed 20 chronic diseases and found a higher risk in adults whose parents had died before they were 16 years old.…”
Section: Early Parental Death and Diseasessupporting
confidence: 77%
“…Many studies have linked parental death with depression. 7,8 However, our data also confirm the negative effects on adult physical health. 6,[14][15][16][17][18] The study by Neeleman et al (2002) 15 analysed 20 chronic diseases and found a higher risk in adults whose parents had died before they were 16 years old.…”
Section: Early Parental Death and Diseasessupporting
confidence: 77%
“…Depression after bereavement is common, with longitudinal assessments indicating that 20–25% of bereaved people develop depression at some point (Galatzer-Levy and Bonanno, 2012; Maccallum et al, 2015; Pham et al, 2018). Prior to DSM-5, clinicians were advised to use caution in diagnosing depression after bereavement because it may result in over-diagnosis in the context of expected levels of grief.…”
Section: Classificationmentioning
confidence: 99%
“…At the same time studies (e.g. Nielsen et al, 2012;Pham et al, 2018) indicate that nearly half of all bereaved children have experienced daily impairments to their daily functioning. Therefore, schools should make it a high priority to offer bereaved children support throughout the difficult experience of loss.…”
Section: Introductionmentioning
confidence: 98%